Uncertainties for pressure-time efficiency measurements - Ramdal, Jørgen; Jonsson, Pontus; Dahlhaug, Ole Gunnar; Nielsen, Torbjørn; Cervantes, Michel (Luleå tekniska universitet, Strömningslära och experimentell mekanik, 2010)
In connection with the pressure-time project at the Norwegian University of Science and Technology and Luleå University of Technology, a number of tests with the pressure-time method have been performed at the Waterpower Laboratory in Trondheim, Norway. The aim is to lower the uncertainty and improve usability of the method. Also a field test at the Anundsjoe power plant in Sweden has been performed. The pressure-time measurement is affected by random uncertainty. To minimize the effect of the random behavior it is found that a correct integration end limit in the integration of the differential pressure is essential. An analysis using 100 different end points for integration show a possible random error as large as 0.6%. A filtration method for finding an appropriate end point is developed and presented. In laboratory, the random behavior of the method can be described since many tests can be performed. During field measurements, this may not be feasible. However, the random uncertainty can be included if the efficiency curve can be described by polynomial regression curves. This method is presented with the Anundsjoe Power Plant measurements. Godkänd; 2010; 20101117 (ponjon)